Anti-Human TraffickingA Descriptive Study of Adult Education Programs in Relationship to Policy and Funding (Empirical) - Shannon Deer; Matthew A. Josefy (Adult Education Research Conference, 2015)
In this study, I describe anti-human trafficking organizations with an educational mission. Organizations vary based on educational approach, location, gender, and age served, and founder’s gender. I categorize the organizations using these factors and illustrate organizations’ characteristics and their impact on funding through descriptive statistics.
Keywords: anti-human trafficking; transnational social learning theory; feminist theory